PENGARUH KOMITE AUDIT, KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, DAN LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Ardila Shintya Ningrum; Yusroni, Nanang; Ricza Irhamni (Universitas Ratu Samban, 2024)
The study aims to determine the significance of the influence of audit committees, institutional ownership, independent commissioners, and leverage on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2016-2018 period. The independent variables in this study are the audit committee, institutional ownership, independent commissioners, and leverage, while the dependent variable is earnings management. Calculation of all variables based on financial statement data obtained from www.idx.co.id.This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The sampling technique used in this study was purposive sampling technique. Samples from this study were 71 company samples during the 2016-2018 period, thus obtained 213 studies. The method used in this research is multiple linear analysis with panel data. The statistical analysis used is the data processing application Eviews 9 and Microsoft Excel 2013. The results of this study indicate that audit committee variables, institutional ownership, independent commissioners, and leverage have no effect on earnings management